2009
DOI: 10.1177/1087057109335679
|View full text |Cite
|
Sign up to set email alerts
|

Can Phage Display Be Used as a Tool to Functionally Identify Endogenous Eat-Me Signals in Phagocytosis?

Abstract: Removal of apoptotic cells and cellular debris by phagocytosis is essential for development, tissue homeostasis and resolution of inflammation. Eat-me signals control the initiation of phagocytosis, holding a key to our understanding of phagocyte biology. Due to lack of functional cloning strategy, eat-me signals are conventionally identified and characterized on a case-by-case basis. To investigate the feasibility of functionally cloning eat-me signals by phage display, we characterize the biological behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 27 publications
(50 reference statements)
0
41
0
Order By: Relevance
“…Human ARPE19 RPE cells were cultured as previously described [8]. Rat RPE-J and human D407 RPE cell lines, gifts from Dr. G. Hoppe (Cleveland Clinic, Ohio), were cultured in Dulbecco's modified essential medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 2 mM L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human ARPE19 RPE cells were cultured as previously described [8]. Rat RPE-J and human D407 RPE cell lines, gifts from Dr. G. Hoppe (Cleveland Clinic, Ohio), were cultured in Dulbecco's modified essential medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 2 mM L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…The question is whether this strategy can be used to identify unknown eat-me signals. We recently demonstrated that T7 phage displaying MEG-E8 or Gas6, two well-characterized eat-me signals, was preferentially phagocytosed and enriched by retinal pigment epithelium (RPE) cells or macrophages, but not by non-phagocytes [8], suggesting that the strategy of phagocytosis-based phage selection is feasible for functional cloning of unknown eat-me signals. However, unlike Ab libraries, cDNA repertoires with unpredictable reading frames and stop codons may not be expressed in correct frames as phage capsid fusion proteins [9].…”
Section: Introductionmentioning
confidence: 99%
“…We recently characterized the feasibility to enrich phagocytosis ligands by phage display (Caberoy et al 2009). The question is whether this approach can be used for identification of unknown RPE phagocytosis ligands.…”
Section: 3 Resultsmentioning
confidence: 99%
“…D407 human RPE and HEK293 cell lines were previously described (Caberoy et al, 2009) and cultured in Dulbeccos's modified essential medium (DMEM) supplemented with 10% FBS and 2 mM L-glutamine (Mediatech, Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%